Kartagener’s Syndrome with Short Stature – A Rare Association - Thoyaj KJ; Chandrik Babu (JK Science)
Kartagener’s syndrome [KS] is a rare, autosomal recessive disease comprising a triad of situs inversus, bronchiectasis and sinusitis. Usually, KS manifest in early childhood and the manifestations include chronic, thick, mucoid rhinorrhoea, recurrent otitis media, wheeze, chronic wet cough with unexplained respiratory distress. Most of the times clinicians would have seen many times before the diagnosis is made. Here with we are reporting a 16-year-old girl who presented with recurrent infections since childhood days, diagnosed as KS at the age of 16 years with short stature due to Growth hormone deficiency.